2012
DOI: 10.1038/leu.2012.141
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD47 antibodies promote phagocytosis and inhibit the growth of human myeloma cells

Abstract: Multiple myeloma is a plasma cell neoplasm residing in bone marrow. Despite advances in myeloma therapies, novel therapies are required to improve patient outcomes. CD47 is highly expressed on myeloma cells and a potential therapeutic candidate for myeloma therapies. Flow cytometric analysis of patient bone marrow cells revealed that myeloma cells overexpress CD47 when compared with non-myeloma cells in 73% of patients (27/37). CD47 expression protects cells from phagocytosis by transmitting an inhibitory sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
180
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(187 citation statements)
references
References 40 publications
5
180
0
2
Order By: Relevance
“…41 Moreover, targeting the CD47-SIRP a axis has now been shown to increase efficacy of several therapeutic antibodies. 42,43 CD47 is described to be highly expressed on CD38 C MM cells, 44 suggesting that inhibition of the CD47-SIRP a axis might be an interesting therapeutic approach in combination with DARA.…”
Section: Discussionmentioning
confidence: 99%
“…41 Moreover, targeting the CD47-SIRP a axis has now been shown to increase efficacy of several therapeutic antibodies. 42,43 CD47 is described to be highly expressed on CD38 C MM cells, 44 suggesting that inhibition of the CD47-SIRP a axis might be an interesting therapeutic approach in combination with DARA.…”
Section: Discussionmentioning
confidence: 99%
“…are sensitive to blocking anti-CD47 antibodies (233,234,(241)(242)(243)(244)(245)(246)(247)(248)(249)(250). This makes CD47 the first protooncogene that is universally expressed in all cancers; its function is known, and blockade of its function is therapeutic.…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 99%
“…Recently a role for PrCR in eliminating living tumor cells has been revealed (1). Several studies have indicated a crucial function of CD47 as an antiphagocytic don't-eat-me signal dominating over PrCR (3)(4)(5)(6)(7)(8)(9)(10). During cancer development, tumor cells up-regulate CD47, which protects them from PrCR (1,3,4,6).…”
mentioning
confidence: 99%